Rancang Bangun Kunci Pintu Otomatis Sistem Rfid Berbasis Arduino Di Ruangan Laboratorium Teknologi Listrik Politeknik Negeri Ketapang - Ivan Suwanda (Electrical Network Systems and Sources, 2023)
The development of technology to replace the human role with a tool or machine, therefore basically the door has been controlled through the program, there are a lot of thefts in homes because the security system does not protect the door of the house and usually only uses commercial keys as security, Current technological advances have led to an innovation to create a sophisticated security system tool that uses a wireless electronic key with RFID.This study uses the Literature Study method, which is a method of collecting data by looking for references that are relevant to the problem to be solved. The reference in question can be from journals, books or articles that discuss the manufacture of door locks using the RFID system.. This research procedure is carried out into 9 stages, namely (1) starting, (2) potential and problems. , (3) information collection, (4) tool design, (5) design validation, (6) tool manufacture, (7) tool testing, (8) data collection and (9) data analysis.Based on the test results, it can be concluded that the simulation of the door safety device can operate properly, according to the design made. The RFID reader used has a frequency of 13.56MHz which is placed in a 2mm thick box that can read ID tags with a maximum distance of 1.8 cm. The solenoid can unlock the door if the ID tag matches the Arduino Nano, the solenoid will lock again within 5 seconds.